Prarancangan Pabrik Biodiesel dari Minyak Biji Karet dengan Kapasitas 100.000 Ton/Tahun - KURNIAWAN, Achmad Annas ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The growing biodiesel industry in Indonesia are quite large, given that the demand for oil is increased so as to reduce dependence on Fossil energy which is not renewable. The main raw material required is 99% methanol as 35,055 tons/year and 408,126 tons/year of rubber seed. As for supporting material, 728 tons/year of NaOH 99%, 201 tons/year of H2SO4 98%, and 1,801 tons/year of H3PO4 are needed. Biodiesel is produced as main product with production capacity of 100,000 tons/year. 7,902 tons/year of glycerol is produced as side product. The process steps are as follows: (i) the reaction between methanol and FFA with sulfuric acid catalyst in a reactive distillation (RD-01), (ii) neutralization of acid catalyst and residual unreacted FFA by NaOH solution, (iii ) separation of salts, (iv) the reaction between methanol and TGS with NaOH catalyst in a reactive distillation (RD-02), and (v) biodiesel and glycerol product purification through liquid-liquid separation process and evaporation . This plant will be established in Balikpapan, East Kalimantan province, on account of raw material oriented. The employees are 188 people and 23,750 m2 of area is needed. 537,536 tons/year of cooling water, 116.878 tons/year of make-up water, 13,865,700 m3/year of compressed air, 34,576,584 m3/year of natural gas, and 2296 kW of electricity are needed to operate the plant. Calculation of economic evaluation results of fixed capital required is $ 29,324,050.42 + Rp18.827.655.468, 17, and working capital of $ 5,114,900.85 + Rp80.123.982.999, 41. At 100% production capacity, the ROI before tax is 23.74%, ROI after tax is 10.36%. POT before tax is 2.96 years, POT after tax is 4.57 years with a BEP of 51.39%, SDP of 27.65%, and 21.44% of DCFRR. Based on consideration of the evaluation results, this biodiesel plant with capacity of 100,000 tons / year is worthy of further analysis.